Fixed-time artificial insemination technology in buffaloes: a review - Kolachi, Hubdar Ali; Zhang, Xiaomeng; Rahimoon, Muhammad Mohsen; Shahzad, Muhammad; Oluwaseun, Ayantoye Jesse; Panhwar, Muhammad Ibrahim; Hassan, Mohammad Farooque; Tawfik Kandil, Omaima Mohammad; Wan, Pengcheng; Zhao, Xueming (Frontiers in Veterinary Science, 2025)
Buffalo occupies a leading position as a major livestock commodity and is the primary milk-producing animal in many countries like Italy, China, India, Pakistan, Bangladesh, and Nepal. Buffalo farming emphasizes the significance of effective reproductive strategies. Among effective reproductive strategy, artificial insemination has a significant influence on herd's genetic progress. Nonetheless, buffaloes exhibit unique reproductive behavior, which complicates the insemination process. These animals demonstrate inconsistent periods (ranging from 6–48 h) of mounting acceptance. Therefore, timed artificial insemination (TAI) has surfaced as a useful technique for advancing buffalo breeding initiatives and omits the need for heat detection. TAI enhances reproductive management and genetic progress in buffaloes by synchronizing estrus and optimizing insemination timing. This review focuses on examining buffalo reproductive physiology, particularly emphasizing estrus synchronization protocols, ovulation, and TAI. We also provide a brief description of the factors influencing TAI success, such as hormonal treatments and environmental conditions. This review underscores TAI's importance identifies areas for further research and development and reinforces its central role in sustainable buffalo farming.